Fuzzy model for clustering open pollinated maize variety released in Indonesia. Issue 1 (April 2020) - Aqil, Muhammad; Andayani, N.N.; Fahdiana, T; Suwardi,
Abstract: Open-pollinated variety (OPV) is a potential gene source for developing new high yielding maize hybrid. Grouping of maize OPV varieties requires a model analysis tool such as the fuzzy clustering in order to identify the similarity measure. The objective of the research was to characterize the similarity among OPV varieties for further research including site-specific OPV development. As many as 35 OPV varieties were assessed and clustered into groups by using fuzzy c means algorithm. The result indicated that fuzzy model clustering enabled to develop a relationship among the OPV maize and morphological traits. Based on the similarity among agronomic characters, OPV maize varieties can be clustered into four group. Group I represent high productivity, drought and disease tolerant varieties. Group II contains maize varieties characterized by late silking and maturity days. Further, Group III represent varieties with the earliest maturity varieties and low grain yield. Group IV indicates the OPV maize having moderate grain yield and susceptible to downy mildew disease. The information on similarity among variety or group can be used for varietal improvement programs such as recombination and molecular based gene introgression not only for maize but also other crops. Our findings also provide insights to understand similarity among each variety, which are considered to be valuable for future OPV breeding programs such as drought, lodging and disease resistant varieties.